The Relationship Between Attitude And Secondary Prevention Behavior In Coronary Heart Disease - Salmi, Dwi Nurul; Serli Wulan Safitri; Adep Junika; Yuyun Efrianti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2025)
Coronary heart disease is a disorder of heart function caused by the narrowing of the coronary arteries or coronary arteries. Coronary heart disease is one of the cardiovascular diseases that causes the highest death, with more than 7.4 million deaths. The purpose of the study: is to determine the relationship between attitudes with behaviour of secondary prevention in coronary heart disease. This type of research uses an analytical survey method with a cross-sectional approach. The sample in this study was conducted through a total sampling technique of 29 people. From the results of the analysis, it was found that there was a significant relationship between attitudes (ρ-value = 0.000) in the behavior of secondary prevention of coronary heart disease. Hospital advice to improve services in hospitals by focusing on services aimed at preventive services through health promotion related to positive attitudes and prevention to reduce risk factors for coronary heart disease to patients, patient's families.